Volumen de la vía aérea superior en diferentes patrones esqueléticos faciales de una población peruana en tomografía computarizada de haz cónico - Paredes Vilchez, Renzo Angel (2020)
Background: Within diagnosis and treatment planning in patients with dentofacial deformities, evaluation of the upper airway is important since it may be altered by facial skeletal pattern or be affected by orthognathic surgery, being the Cone Beam Computed Tomography (CBCT) the best diagnostic tool for evaluation of airway due to its precision and predictability. Objective: To evaluate upper airway volume in different facial skeletal patterns of a peruvian population in CBCT. Materials and methods: 60 tomographies were evaluated through the PLANMECA Romexis Viewer program, where volume in nasopharynx, oropharynx and hypopharynx was measured. according to facial skeletal pattern and sex. Results: 45% were males and 55% females. It was observed that the highest average volume was found in patients with Class III with 7.37 cm³, 19.14 cm³ and 5.65 cm³ in nasopharynx, oropharynx and hypopharynx respectively. In hypopharynx it was observed that in class II and III the mean volume values are significantly higher in males (P <0.05). In addition, significance of facial skeletal patterns was found in oropharynx and hypopharynx (P <0.05). Conclusion: The average upper airway volume in patients with Class III facial skeletal pattern is greater than in Class I and II, being significant in oropharynx.